PALEOBIOLOGY OF THE NEOPROTEROZOIC (UPPER RIPHEAN) SHORIKHA AND BUROVAYA SILICIFIED MICROBIOTAS, TURUKHANSK UPLIFT, SIBERIA - Sergeev V.N. (My University, 2001)
Diverse assemblages of silicified microfossils have been detected in lenses of black chert within peritidal carbonates of the Neoproterozoic (Upper Riphean) Shorikha and Burovaya formations, Turukhansk Uplift, northeastern Siberia. These microbiotas are represented by 19 species of simple filamentous and coccoidal microfossils, multicellular trichomes, and thick-enveloped sphaeromorphic and acanthomorphic acritarchs. Microfossils include both prokaryotic (possibly cyanobacterial) and eukaryotic (mainly phytoplanktonic) microorganisms. The eukaryotes in these formations are relatively diverse—the result of an explosive radiation near the Meso-Neoproterozoic boundary. The discovery of abundant phytoplanktonic microorganisms in the Shorikha and Burovaya cherts increases the biostratigraphical potential of Proterozoic silicified microbiotas and fills a gap in the paleontological record of the Turukhansk Uplift, a potential candidate for the stratotype of the Meso-Neoproterozoic boundary. The affinities of the formally described taxa are postulated as follows: Oscillatoriaceae: Eomicrocoleus crassus Horodyski and Donaldson, 1980; Oscillatoriopsis obtusa Schopf and Blacic, 1971; O. media Mendelson and Schopf, 1982; Oscillatoriaceae or Nostocaceae: Siphonophycus robustum (Schopf, 1968); S. typicum (Hermann, 1974); S. solidum (Golub, 1979); Nostocaceae or Stigonemataceae: Archaeoellipsoides minor (Golovenoc and Belova, 1984); Chroococcaceae: Gloeodiniopsis lamellosa Schopf, 1968, Eosynechococcus grandis Hofmann, 1976; Incertae sedis: Scissilisphaera gradata Green, Knoll and Swett, 1989; Myxococcoides minor Schopf, 1968; M. inornata Schopf, 1968; M. stragulescens Green, Knoll, and Swett, 1989; Myxococcoides sp.; Pterospermopsimorpha? sp.; Shorikhosphaeridium knolli new genus and species; Leiosphaeridia jacutica (Timofeev); problematic ellipsoidal forms; and problematic spiny forms.
Keywords: Silicified microfossils; Neoproterozoic; Riphean; Turukhansk Uplift; Siberia; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Neoproterozoic; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей